2014
DOI: 10.1016/j.envint.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Learning from 8 years of regional cyanobacteria observation in Brittany in view of sanitary survey improvement

Abstract: Cyanobacteria and cyanotoxins have been more and more studied during the last decades with regard to environment and health issues. More recently the consequences of climate change reinforced the need for research in view of a better management of cyanobacteria blooms. In this context the exploitation of the water quality survey of 26 recreational lakes in Brittany (north western France) between 2004 and 2011 is reported in this paper in order to encompass spatial and interannual patterns of cyanobacteria deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…All data together, maximal cell densities ranged every year from 1.9 to 6.5 10 6 cell/ml, with weekly average values from 10 600 to 452 000 cell/ml. Quantile distributions of cell densities and WHO alert thresholds have already been described in a previous work (Pitois et al, 2014a). To summarize, the mean weekly values tended to increase regularly from 2004 to 2011, in particular because of an increase of the lower, spring densities ( Figure 2).…”
Section: 1-cyanobacteria Occurrences and Biomasssupporting
confidence: 65%
“…All data together, maximal cell densities ranged every year from 1.9 to 6.5 10 6 cell/ml, with weekly average values from 10 600 to 452 000 cell/ml. Quantile distributions of cell densities and WHO alert thresholds have already been described in a previous work (Pitois et al, 2014a). To summarize, the mean weekly values tended to increase regularly from 2004 to 2011, in particular because of an increase of the lower, spring densities ( Figure 2).…”
Section: 1-cyanobacteria Occurrences and Biomasssupporting
confidence: 65%
“…Preliminary studies have already shown that the local oceanic-type climate of Brittany has been warming up for the last 30 years [32], and that cyanobacteria are widely encountered in most recreational lakes [33]. In the same time, available interannual monitoring data tend to show that cyanobacteria are increasingly present, with expansion parameters related to climate and lake morphology [34]. The present study is based on the observation that climate evolution at regional scale is of the same magnitude of latitudinal meteorological gradients, leading to the hypothesis that a comparison between eastern and western Brittany can give insights of the potential future situation regarding cyanobacteria (species composition, toxin occurrences) in a 30-year timespan.…”
Section: Introductionmentioning
confidence: 99%
“…One consequence of this high agriculture pressure is the high overall soil nitrogen (N) and P surpluses (about 50.0 ± 26.6 kg N ha -1 yr -1 and 22.5 ± 12.7 kg P ha -1 yr -1 , respectively) in Brittany (Guillemot et al, 2021), leading to high stocks in soils. Associated with a globally impermeable bedrock resulting in shallow water circulation and spatially extended wetland areas (Dupas et al, 2013), these high surpluses are causing the widespread eutrophication of both its continental and coastal waters (Charlier et al, 2007;Pitois et al, 2014;Guillemot et al, 2021;Schreyers et al, 2021).…”
Section: Study Area Sampling Locationsmentioning
confidence: 99%